2002
DOI: 10.1177/145749690209100206
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of Primary Melanoma

Abstract: We conclude that the prognosis of primary melanoma has improved in Finland in the last decades being in line with a global tendency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The international data for incidence and mortality for prostate cancer also vary by ethnic group [2,3]; prostate cancer incidence and mortality rates among Black American men are higher than any other racial groups in the US and about twice those in White American men [4,5]. Blacks in the US are also more likely to present with advanced prostate cancer.…”
Section: Introductionmentioning
confidence: 98%
“…The international data for incidence and mortality for prostate cancer also vary by ethnic group [2,3]; prostate cancer incidence and mortality rates among Black American men are higher than any other racial groups in the US and about twice those in White American men [4,5]. Blacks in the US are also more likely to present with advanced prostate cancer.…”
Section: Introductionmentioning
confidence: 98%
“…Several clinical and routine histological factors of primary melanomas with prognostic significance have been described, that is, tumor thickness according to Breslow, Clark levels, ulceration, localization, presence of tumor-infiltrating lymphocytes, gender, and patients' age. 1 By far, the most significant and consistent prognostic factor in all series over the past 20 years is Breslow thickness of the primary melanoma. 2 Kanitakis et al 3 have recently found that CD10 is more frequently expressed in metastatic than in primary melanoma.…”
mentioning
confidence: 99%
“…In the early 1990 s, surgical margins diminished to 1-3 cm, and elective lymphadenectomy was less frequent [11]. Earlier, the radical operation required up to 5 cm margins, and high-risk patients also underwent elective lymphadenectomy.…”
Section: Excision Of Primary Melanoma and Management Of Lymph Nodesmentioning
confidence: 99%